A new species of Poptella (Characiformes: Characidae: Stethaprioninae) from the Rio Juma, Rio Madeira basin, Brazil - Garcia-Ayala, James R. [UNESP]; Benine, Ricardo C. [UNESP] (FapUNIFESP (SciELO), 2019)
A new species of Poptella is described from the Rio Juma, a tributary of the lower Rio Aripuanã, Rio Madeira basin, Amazonas, Brazil. The new species is distinguished from all congeners, except P. brevispina, by having a lower number of scale rows between the lateral line and dorsal-fin origin (7 vs. 8-10). The new species can be readily distinguished from P. brevispina by the lower number of branched dorsal-fin rays (9 vs. 10). This is the first description of a new species of Poptella since the revisionary study of the Stethaprioninae, published 30 years ago.
Keywords: Amazon; Biodiversity; Freshwater fish; Stethaprionini; Taxonomy